Analysis of thermal properties of concrete made using aggregate from sanitary ceramic wastes - Zegardło, Bartosz; Halicka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
This paper is a continuation of research on concrete made using aggregates derived from sanitary ceramic wastes. Previous studies have shown that it is high strength concrete resistant to high temperatures. Looking for the optimal use of such concrete tests and analysis of its thermal accumulation were executed. The behavior during cooling of this concrete in comparison to other building materials was observed. The calculations of its thermal accumulation were made. It was found that concrete made on the basis of aggregate from waste sanitary ceramics can be recommended as a heat accumulating material.